Dimensi Kepemimpinan Transformasional dalam Perspektif al-Qur’an - Nur Ulwiyah; Binti Maunah; Zainul Arifin (Universitas Pesantren Tinggi Darul 'Ulum, 2021)
The purpose of this article is to examine the dimensions of transformational leadership in the perspective of the Qur’ān as a form of leadership that is considered the closest to the ideal. This article focuses the discussion on the concept of dimensions in language and terms, the dimensions of transformational leadership in the frame of Bass theory, and the discussion of verses of the Qur’ān containing the substance of the dimensions of transformational leadership. The method used in the writing of this article is the study of literature by collecting relevant literature, then analyzed, compared, and drawn the meeting point line to obtain the integrity of understanding. Furthermore, the results of this article study there are three, namely: first, the word “dimension” has the meaning of size, whether related to many, large, wide, long, width, or height of an object. Object of study, discussion, or object of view. And from the number of dimensions, it can be known an object with one dimension, two dimensions, three dimensions, four dimensions, even multi-dimensional. Second, bass's transformational leadership dimension is four, known as 4I, idealized influence, inspirational motivation, intellectual stimulation, and individual concideration. Bass’ dimensions can be widely adapted from a variety of approaches and viewpoints of the characters against the background of their respective leadership principles. Third, bass transformational leadership dimension in line with the values prescribed by Allah Almighty in the Qur’ān and the Sunnah of the Prophet (s).